Providing Stimulus to Animals Results in Response in the form of Animal Behavior Patterns to the Environment: A Literature Review - Abdul Razak; Suci Fajrina; Silvira Ilhami; Tri Putri Wahyuni (Science Journal Get Press, 2024)
Behavior is an organism's response to internal and external stimuli. By definition, behavior is an action performed by a living being in reaction to a stimulus. A consistent pattern of response to specific stimuli is categorized as behavior. An animal's ability to survive is reflected in these behavioral patterns. Each animal species has a unique way of acting, corresponding to their anatomical structure. Therefore, it is crucial to study animal behavior patterns in depth, given their critical role in maintaining ecosystem sustainability and balance. This research aims to investigate how the provision of stimuli to animals generates responses in the form of behavioral patterns towards their environment. By writing this research, it is hoped that the general public can understand more about animal behavior patterns. This research method is a literature review or literature review through several research articles, this review is done by searching from a database in the form of Google Scholar and obtaining 5 research articles.